Protective Effects of Smoke-free Legislation on Birth Outcomes in England: A Regression Discontinuity Design. Issue 6 (November 2016) - Bakolis, Ioannis; Kelly, Ruth; Fecht, Daniela; Best, Nicky; Millett, Christopher; Garwood, Kevin; Elliott, Paul; Hansell, Anna L.; Hodgson, Susan
Abstract : Background: Environmental tobacco smoke has an adverse association with preterm birth and birth weight. England introduced a new law to make virtually all enclosed public places and workplaces smoke free on July 1, 2007. We investigated the effect of smoke-free legislation on birth outcomes in England using Hospital Episode Statistics (HES) maternity data. Methods: We used regression discontinuity, a quasi-experimental study design, which can facilitate valid causal inference, to analyze short-term effects of smoke-free legislation on birth weight, low birth weight, gestational age, preterm birth, and small for gestational age. Results: We analyzed 1, 800, 906 pregnancies resulting in singleton live-births in England between 1 January 2005 and 31 December 2009. In the 1 to 5 months following the introduction of the smoke-free legislation, for those entering their third trimester, the risk of low birth weight decreased by between 8% (95% confidence interval [CI]: 4%, 12%) and 14% (95% CI: 5%, 23%), very low birth weight between 28% (95% CI: 19%, 36%) and 32% (95% CI: 21%, 41%), preterm birth between 4% (95% CI: 1%, 8%) and 9% (95% CI: 2%, 16%), and small for gestational age between 5% (95% CI: 2%, 8%) and 9% (95% CI: 2%, 15%). The estimated impact of the smoke-free legislation varied by maternal age, deprivation, ethnicity, and region. Conclusions: The introduction of smoke-free legislation in England had an immediate estimated beneficial impact on birth outcomes overall, although we did not observe improvements across all age, ethnic, or deprivation groups. See video abstract athttp://links.lww.com/EDE/B85 . Abstract : Supplemental Digital Content is available in the text.